2018
DOI: 10.1029/2018tc005047
|View full text |Cite
|
Sign up to set email alerts
|

Present‐Day Deformations of the Jura Arc Inferred by GPS Surveying and Earthquake Focal Mechanisms

Abstract: This study presents a compilation of more than 40 years of seismotectonic data, including 54 computed focal mechanisms, combined with 15 years of GPS data coming from a dense network of 35 permanent GPS stations within the Jura arc and its vicinity. These data are compared to previous available geomorphological, geophysical, and structural studies in order to discuss the 3D distribution of the deformation within the Jura arc. GPS data show coherent schemes in terms of velocities and allowed to discriminate bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 89 publications
6
39
0
Order By: Relevance
“…N-S normal faults are located, mainly on the external border of the arc and within the Rhine and Bresse grabens and the RBTZ. The Jura massif and the Bresse graben are currently affected by NNW-SSE shortening and strike-slip tectonic regime with the maximum horizontal stressoriented NW-SE [Rabin et al, 2018]. Actually, several studies have highlighted the complexity and variability of the tectonic style in the area according to the present-day coupling/uncoupling between the basement and its sedimentary cover [e.g.…”
Section: The Jura Massif and The Bresse Grabenmentioning
confidence: 99%
See 1 more Smart Citation
“…N-S normal faults are located, mainly on the external border of the arc and within the Rhine and Bresse grabens and the RBTZ. The Jura massif and the Bresse graben are currently affected by NNW-SSE shortening and strike-slip tectonic regime with the maximum horizontal stressoriented NW-SE [Rabin et al, 2018]. Actually, several studies have highlighted the complexity and variability of the tectonic style in the area according to the present-day coupling/uncoupling between the basement and its sedimentary cover [e.g.…”
Section: The Jura Massif and The Bresse Grabenmentioning
confidence: 99%
“…Actually, several studies have highlighted the complexity and variability of the tectonic style in the area according to the present-day coupling/uncoupling between the basement and its sedimentary cover [e.g. Becker, 2000, Lacombe and Mouthereau, 2002, Madritsch et al, 2008, Rabin et al, 2018.…”
Section: The Jura Massif and The Bresse Grabenmentioning
confidence: 99%
“…• Jura and Upper Rhine Graben: Predominantly strike-slip deformation with a maximum principal stress (s1) oriented NW-SE Rabin et al, 2018).…”
Section: Previous Studies and Limitationsmentioning
confidence: 99%
“…As an example of a possible seismotectonic study using complementary datasets such as geodetic data (e.g., Rabin et al, 2018;Walpersdorf et al, 2018), a comparison is shown in Figure 8d with horizontal Global Positioning System (GPS) strain rates. This example corresponds to a strain rate model derived from GPS velocities smoothed over characteristic distances of ca.…”
Section: Northern Alps-jura-vosgesmentioning
confidence: 99%
“…A total of 216 focal mechanisms (Figure 4) have been used in this study from the new focal mechanism database FMHex20 of RESIF by Mazzotti et al [2021]. For the region under study, the nodal plane parameters have been either determined by Delouis et al [1993], Delacou et al [2004], Vannucci and Gasperini [2004] and Rabin et al [2018], or estimated by the Seismic Observatory of Northeast France at EOST for earthquakes with low magnitude (2.5 to 4.0). The magnitude of these events ranges [Masson et al, 2021].…”
Section: Focal Mechanisms and Tensors Of Stress And Strain Ratementioning
confidence: 99%